Faktor-Faktor Yang Mempengaruhi Perilaku Pengelolaan Keuangan Mahasiswa Politeknik Caltex Riau - Hamdani Arifulsyah; Heri Ribut Yuliantoro; Abdi Bhayangkara (Universitas Pamulang, 2023)
This study aims to determine whether financial literacy represented by knowledge of basic financial skills, savings and credit, investment, risk management and the campus environment has an effect on financial management among students of the Caltex Riau Polytechnic. The data used is the result of a questionnaire distributed to all Caltex Riau Polytechnic Students. The research method used to analyze data and test hypotheses is multiple linear regression. The population of this study were all students of the Caltex Riau Polytechnic, totaling 2,055 people and 130 people who filled out the questionnaire, of this number, they had met the minimum number required in the Slovin formula. The results of this study indicate that knowledge of basic financial skills and risk management both have an effect on student financial management, while savings and credit, investment and campus environment each have no effect on student financial management. Keywords: Knowledge of basic financial skills, savings and credit, investment, risk management and the campus environment and student financial management